2015
DOI: 10.2967/jnumed.115.160648
|View full text |Cite
|
Sign up to set email alerts
|

68Ga-NOTA-PRGD2 PET/CT for Integrin Imaging in Patients with Lung Cancer

Abstract: This study was designed to assess the diagnostic value of 68Ga-NOTA-PRGD2 (NOTA-PRGD2 is NOTA-PEG4-E[c(RGDfK)]2) PET/CT in lung cancer. Methods Ninety-one patients (48 men and 43 women; age, 22–82 y) with suspected lung lesions on CT were enrolled with informed consent. Immediately after intravenous injection of 117.7 ± 37.7 MBq of 68Ga-NOTA-PRGD2, 15 patients underwent dynamic whole-body PET/CT scans for 1–2 h, and the remaining 76 patients underwent whole-body PET/CT scans at 30 ± 10 min after bolus injecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 37 publications
1
48
0
Order By: Relevance
“…The development of radio-labeled peptide probes, such as RGD and NGR, for diagnostic and therapeutic applications, has rapidly expanded in the last decades (34)(35)(36)(37). On the aspect of clinical practice, the safety and the applicability of these probes have been well established in lung cancer (38)(39)(40), brain metastases (41), breast cancer (42) and rheumatoid arthritis (43). Even though HCCs are worldwide malignant tumors with high incidence of morbidity, there has been little progress in their detection by radio-labeled probes.…”
Section: Discussionmentioning
confidence: 99%
“…The development of radio-labeled peptide probes, such as RGD and NGR, for diagnostic and therapeutic applications, has rapidly expanded in the last decades (34)(35)(36)(37). On the aspect of clinical practice, the safety and the applicability of these probes have been well established in lung cancer (38)(39)(40), brain metastases (41), breast cancer (42) and rheumatoid arthritis (43). Even though HCCs are worldwide malignant tumors with high incidence of morbidity, there has been little progress in their detection by radio-labeled probes.…”
Section: Discussionmentioning
confidence: 99%
“…Intermediate uptake is found in the liver, spleen, and intestines. Reproduced with the permission from [5,45,47,190,[207][208][209][210].…”
Section: Integrinsmentioning
confidence: 99%
“…68 Ga NOTA-RGD is the first 68 Ga-labeled integrin-targeting compound for which initial clinical data is available. A study by Zheng et al suggested that the diagnostic value of 68 Ga-NOTA-PRGD2 for lung cancer diagnosis was comparable to 18 F-FDG with a significant advantage over 18 F-FDG in identifying metastatic lymph nodes with greater specificity (67).…”
Section: Angiogenesis In Lung Cancermentioning
confidence: 99%